Determination of spectral decay parameter and Quality factor in Kermanshah region, NW Iran - DELOUEI, Mehdi Nouri; GHEITANCHI, Mohammad-Reza (Contributions to Geophysics and Geodesy, 2021)
Among important parameters in simulation of earthquake data in high frequencies are the high frequency spectral amplitude decay and the Quality factor. Amplitude spectral decay is determined by the Kappa parameter (K) and the Quality factor (Q) which is usually expressed by a power relation of frequency (f) as Q = Q0 f n, where Q0 is Q at 1 Hz. The 2017 Sarpol-e-Zahab earthquake with magnitude Mw = 7.3 in Kermanshah province near the Iran-Iraq border caused extensive destruction and heavy human loss. Thus, the study of different aspects of this event is of high importance. In this paper an attempt is made to partly explain the attenuation properties of this region in Zagros suture zone by determining the Kappa and the Quality factors in this region. In this study, accelerograph records of aftershocks of the above-mentioned earthquake have been analysed. The best linear fit for the Kappa, based on the distance (R) in km, is estimated as: K = 0.0005 R + 0.034 for the horizontal component, which exhibits increase with increasing epicentral distance. The correlation of the Quality factor was also found as Q = 88.6 f 0.8, which is in accordance with an active tectonic region.